Diagnostic Approach to Congenital Cystic Masses of the Neck from a Clinical and Pathological Perspective - Amanda Fanous; Guillaume Morcrette; Monique Fabre; Vincent Couloigner; Louise Galmiche-Rolland (MDPI AG, 2021)
Background: neck cysts are frequently encountered in pediatric medicine and can present a diagnostic dilemma for clinicians and pathologists. Several clinical items enable to subclassify neck cyst as age at presentation, anatomical location, including compartments and fascia of the neck, and radiological presentation. Summary: this review will briefly describe the clinical, imaging, pathological and management features of (I) congenital and developmental pathologies, including thyroglossal duct cyst, branchial cleft cysts, dermoid cyst, thymic cyst, and ectopic thymus; (II) vascular malformations, including lymphangioma. Key Messages: pathologists should be familiar with the diagnostic features and clinicopathologic entities of these neck lesions in order to correctly diagnose them and to provide proper clinical management.